“INDONESIA COULD NEVER”: VICARIOUS POLITICAL ENGAGEMENT AND THE DIGITAL SPECTRE OF COMPARISONS IN INDONESIAN NETIZENS’ DISCOURSE ON ZOHRAN MAMDANI - Muhammad Rafly Akbar; Wichitra Yasya (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines how a non-diasporic public in the Global South engages with a foreign election in which it holds no vote, no residence, and no direct material stake. Rather than asking how Indonesian netizens represent Zohran Mamdani, the first Muslim Mayor of New York City, it asks what talking about Mamdani does for these netizens as members of their own polity, and develops the concept of comparative civic imagination: the use of a foreign political figure as a discursive instrument for evaluating, criticising, and re-imagining one’s own democracy. The study applies qualitative Computer-Mediated Discourse Analysis (CMDA) to public Indonesian-language discourse about Mamdani on platform X between 1 November 2025 and 30 June 2026, drawing on a purposively constructed corpus of 213 units—134 citizen-account units as the analytical core and 79 media-account units as contextual triangulation—recoded by comparative function and affective register rather than by stance toward the figure. The findings show that Indonesian netizens engage Mamdani through a comparative architecture organised by the vernacular frame “Mamdani Indonesia” (45% of citizen units) and enacted through three repertoires: analogical personification, institutional benchmarking, and counterfactual transposition. The discourse is animated by civic despair—crystallised in the idiom “Indonesia could never”—which operates as a participatory rather than an apathetic affect, while a domestic value-compatibility filter of doctrinal, sectarian, and purity tests renders the admired model discursively non-transferable, closing a recursive loop theorised here as a digitally networked spectre of comparisons. The article shifts the analysis of transnational digital engagement away from cosmopolitan and diasporic assumptions toward the vicarious engagement of non-diasporic publics, re-theorises despair as a mode of civic engagement, and recovers Benedict Anderson’s spectre of comparisons for platform-era political communication in the Global South.